A preliminary study on enhancing safety of contact features in the terrain park - Dickson, T. J.; Terwiel F. A. (Journal of Science and Medicine in Sport, 2021)
Objectives: Terrain park riders use contact features such as fun boxes and rails. Typical fun box and rail features have a design characteristic that can be changed to improve safety. Fun box edge coping and edges of rails are typically constructed of soft steel. Ski/snowboard edges (HRC50) can easily become engaged in the softer metal, causing a chip to develop, suddenly stopping the rider, probably causing a fall and possible injury. The aim of the study is to examine the effect of terrain park running surface hardness on chip development. Design: Testing on steel specimens was performed to research chip development generated by a ski/snowboard edge on steel used in the construction of contact features and on steel that is proposed for such use. An apparatus was constructed to simulate a ski/snowboard edge moving perpendicular to the long axis of coping or rail edge. Methods: The author performed observation, photographic documentation, metallurgical testing and environmental testing of various contact features at different ski area terrain parks. Several steel specimens of varying hardness were tested at various load levels to study the propensity of chip development by ski/snowboard edges. Results: Testing of steel samples showed that increasing the hardness of the rail steel or coping steel reduced the propensity for a ski/snowboard edge to engage in the coping or rail. Conclusions: Increasing steel coping and rail contact surface hardness to HRC 50 and above will likely reduce engagement by steel snowboard/ski edges, which in turn is expected to reduce the chance of a fall and injury.